THE EFFECT OF TRANSFORMATIONAL LEADERSHIP ON FACULTY PERFORMANCE THROUGH SELF-EFFICACY AND SELF-DIRECTED LEARNING IN THE ERA OF DIGITAL TRANSFORMATION AT RELIGIOUS HIGHER EDUCATION INSTITUTIONS - Jumira Warlizasusi; Zulkarnain Zulkarnain; M. Ramadani; Ifnaldi Ifnaldi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Faculty performance is a strategic indicator of higher education quality, particularly at religious universities that face structural, cultural, and academic challenges, as well as the demands of digital transformation in the delivery of higher education. This study aims to analyze the influence of transformational leadership on faculty performance by examining the mediating roles of self-efficacy and self-directed learning. This study employs an exploratory quantitative approach involving 116 faculty members at public religious universities in Indonesia. Data were collected via a structured questionnaire and analyzed using Structural Equation Modeling (SEM). The results indicate that transformational leadership has a positive and significant influence on faculty performance, both directly and indirectly through self-efficacy and self-directed learning. Self-efficacy was found to act as a psychological mediator that strengthens lecturers’ engagement in self-directed learning, thereby supporting their ability to adapt to the demands of technology-based teaching, research, and community service—which, in turn, leads to improved lecturer performance in fulfilling the Tri Dharma of Higher Education. These findings underscore the importance of transformational leadership focused on psychological empowerment and strengthening faculty members’ learning capacity in navigating the dynamics of digital transformation. This study provides an empirical contribution to the development of higher education management, particularly in formulating sustainable leadership strategies capable of strengthening the readiness of institutions and faculty members to navigate the digital era at religious universities.